ISSUES OF LEGAL SECURITY OF MILITARY SERVICE, ACCOUNTING AND MOBILIZATION OF PUBLIC SERVANTS (ON THE EXAMPLE OF THE POLICE, SSES, SBI) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the problem of individual provisions of the Draft Law on Amendments to Certain Legislative Acts of Ukraine on Certain Issues of Military Service, Mobilization, and Military Registration No. 10449 dated January 30, 2024, as a result of which a number of significant shortcomings of the specified document were identified, and a number of proposals were formulated improvement of its content. First of all, the explanatory note does not substantiate the expediency of making changes to the Laws of Ukraine «On Civil Service», «On the Prosecutor's Office», «On the National Police», etc., which led to legal errors, illogical proposals and the possibility of violation of the constitutional rights and freedoms of citizens. Secondly, it is advisable to exclude from the final and transitional provisions of the specified draft law the provision that: «Male citizens who are serving in the National Police of Ukraine, the Judicial Security Service, the State Bureau of Investigation, the Bureau of Economic Security of Ukraine, bodies and units of civil protection , of the State Criminal Enforcement Service of Ukraine are obliged within 60 days from the date of entry into force of the Law to enter the military register of conscripts in the territorial centers of recruitment and social support at their place of residence;», leaving the current wording of the relevant paragraph of part 1 with respect to this norm Art. 23 of the Law of Ukraine «On Mobilization Training and Mobilization». Thirdly, the norm regarding the restriction of the right to public service for men under the age of 60 who have not completed basic military training or military service: 1) violates Art. 38 of the Constitution of Ukraine; 2) contradicts Clause 7, Part 1, Art. 4 of the Law of Ukraine «On Civil Service»; 3) contains signs of discrimination based on gender and age.
Keywords: martial law; mobilization; state service; public service; service; police; State Emergency Service; State Bureau of Investigation